2011
DOI: 10.1186/1471-2296-12-73
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain among homeless persons: characteristics, treatment, and barriers to management

Abstract: BackgroundLittle information is available on the problem of chronic pain among homeless individuals. This study aimed to describe the characteristics of and treatments for chronic pain, barriers to pain management, concurrent medical conditions, and substance use among a representative sample of homeless single adult shelter users who experience chronic pain in Toronto, Canada.MethodsParticipants were randomly selected at shelters for single homeless adults between September 2007 and February 2008 and screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 15 publications
4
61
2
5
Order By: Relevance
“…In this regard, prior research has linked housing instability to both high pain prevalence and multiple barriers to care. [28][29][30][31][32] Consistent with prior studies, [33][34][35] bivariate analyses found that pain endorsement was strongly associated with psychological distress among this sample of substance users. Individuals with pain, regardless of treatment status, exhibited higher symptom levels for both depression and anxiety, compared to the pain-free.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this regard, prior research has linked housing instability to both high pain prevalence and multiple barriers to care. [28][29][30][31][32] Consistent with prior studies, [33][34][35] bivariate analyses found that pain endorsement was strongly associated with psychological distress among this sample of substance users. Individuals with pain, regardless of treatment status, exhibited higher symptom levels for both depression and anxiety, compared to the pain-free.…”
Section: Discussionsupporting
confidence: 75%
“…The relatively common selection of non-opioid medications may reflect caution among health care providers and prescribers treating a population with known substance abuse issues. 28 Among our vulnerable sample of socioeconomically disadvantaged HIV-positive substance users, pain likely arose from multiple sources, including aging, long-standing participation in street lifestyles that entail drug use and exposure to violence, the presence of multiple chronic health conditions, as well as poverty-driven limitations on health care access and basic subsistence needs. Our bivariate analyses demonstrated that food and housing insecurity were significantly associated with pain endorsement.…”
Section: Discussionmentioning
confidence: 99%
“…The association between substance use disorders and exits builds on literature describing a dearth of Housing First outcome data for consumers with severe substance use disorders (14). Injection drug use is the strongest predictor of HCV (35), and substance use disorders are highly prevalent among homeless consumers with chronic pain (36). Associations between these diagnoses and exiters may reflect an underlying association with substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Une nuit, on en a dénombré 5 000 à Toronto, 900 à Ottawa et 2 700 à Vancouver (Hwang, et collab., 2011). Globalement et sur une base annuelle, on estime que le nombre de sans-abri varie entre 150 000 et 300 000 au Canada (Hwang, et collab., 2011).…”
Section: Introductionunclassified
“…Une nuit, on en a dénombré 5 000 à Toronto, 900 à Ottawa et 2 700 à Vancouver (Hwang, et collab., 2011). Globalement et sur une base annuelle, on estime que le nombre de sans-abri varie entre 150 000 et 300 000 au Canada (Hwang, et collab., 2011). Le dénombrement des sans-abri au pays a commencé en 1987 via les travaux du Conseil canadien de développement social (Begin, et collab., 1999).…”
Section: Introductionunclassified